The disparity between beliefs towards oral interaction and classroom performances: the case of senior secondary school EFL teachers’ in Bishoftu city administration, Ethiopia - Tesfa Bella Defa; Abebe Damtew Berlie (Erudita: Journal of English Language Teaching, 2026)
Teachers’ attitudes direct their actions in classrooms. However, there are conditions impeding them to perform accordingly. Hence, this study investigates the contradiction between senior secondary school EFL teachers’ attitudes on the significances of oral interaction in promoting students’ language proficiency and their classroom performances. It also aims at spotting the challenges which obstruct the teachers to employ oral interaction the ways they perceive it should be. To do so, qualitative approach, case study design was used. Data were gathered from six purposefully selected senior secondary school EFL teachers through observations and interviews. The data obtained were organized thematically and analyzed qualitatively. The results show that although senior secondary school EFL teachers recognize the significance of oral interaction in advancing students’ English language proficiency, they do not use oral interaction as a methodological tool during instructions. The main obstructions that impede them are related to the students, the classroom facilities, the instructional materials, and the teachers themselves. The results have dual implications: first, they contribute to the emergent body of research on the deteriorating students’ oral proficiency skills and teachers’ methodological acquaintances. Second, they justify the necessity for prerequisite actions worth taken to help teachers in solving the problems before assigning the entire responsibility to them for students’ low English language proficiency.